Evolving Landscape of Virtual Exchange: Findings from the Third Global Survey - Kastler, Kyle; Bhandari, Rajika; Ramos, Melquin (International Higher Education, 2024)
Against a backdrop of significant shifts in education and exchange globally, virtually exchange had continued to grow both in scale, scope, and complexity. Based on a third (2022) in a series of annual global virtual exchange surveys by the Stevens Initiative, this article presents key findings about potential growth in global virtual exchange; the context and nuances of virtual exchanges around the world; and implications for program administrators, campus leaders, and decision-makers.